Perancangan Asic (Aplikasi Siaga Covid-19) Pada Universitas Katolik Santo Thomas dengan Metode Prototyping - Harianja, Andy Paul; Gea, Fransiska Farina; Rumahorbo, Andreas (MEANS (Media Informasi Analisa dan Sistem), 2022)
Saint Thomas Catholic University which is a private university located in the city of Medan, North Sumatra. Currently there is no integrated information related to Covid-19 at the Catholic University of Saint Thomas in the form of information on the list of academics who are open or undergoing independent isolation, as well as a monitoring center for visitor activities carrying out activities on campus, in addition to announcements regarding vaccines in the campus environment are still being made via WA (whats app) and other social media like instagram and facebook. Therefore, it is necessary to design an application that manages vaccine data, covid-19 information to the use of campus activities during the pandemic. The application of the Prototyping method in this design will help provide an overview of the system designed to user needs more quickly. The application that is built can provide convenience for stakeholders in the campus environment with lists that can be viewed through the application, as well as facilitate monitoring of visits to campus by filling in forms made by visitors and self-reporting menus or having recovered.